Analysis of Natural Resource Management in Langkat Regency: Impact on the Local Economy - Tarigan, Nur M. Ridha; Budihartini, Dewi; Suprayitno, Eddi; Gusmiati, Yesi (Medan Resource Center, 2024)
This study analyzes natural resource management in Langkat Regency and its impact on the local economy. Using qualitative and quantitative approaches, this study evaluates the implementation of regulations, environmental impacts, distribution of economic benefits, and public perception of natural resource management. The results show that although the mining and plantation sectors contribute significantly to Regional Original Revenue (PAD), economic benefits are not evenly distributed, and many local communities experience a decline in welfare. Intensive exploitation of natural resources has led to significant environmental damage, such as deforestation and water pollution, disrupting the balance of local ecosystems. Weak regulatory implementation and lack of community participation in natural resource management exacerbate this situation. This research suggests improvements in supervision, increased community participation, adoption of environmentally friendly technologies, and policy revisions to achieve more sustainable and equitable management of natural resources. With these steps, it is hoped that Langkat Regency can improve the welfare of the local community more evenly and preserve the environment for future generations.